Plasma biochemical and PCV ranges for healthy, wild, immature hawksbill (Eretmochelys imbricata) sea turtles. (14th June 2014) - Whiting, S. D.; Guinea, M. L.; Fomiatti, K.; Flint, M.; Limpus, C. J.
Abstract : In recent years, the use of blood chemistry as a diagnostic tool for sea turtles has been demonstrated, but much of its effectiveness relies on reference intervals. The first comprehensive blood chemistry values for healthy wild hawksbill (Eretmochelys imbricata) sea turtles are presented. Nineteen blood chemistry analytes and packed cell volume were analysed for 40 clinically healthy juvenile hawksbill sea turtles captured from a rocky reef habitat in northern Australia. We used four statistical approaches to calculate reference intervals and to investigate their use with non‐normal distributions and small sample sizes, and to compare upper and lower limits between methods. Eleven analytes were correlated with curved carapace length indicating that body size should be considered when designing future studies and interpreting analyte values.